Dextre, Juan Carlos; Hughes, Mike y Bech, Lotte (2013). Cyclists & Cycling Around the World. Creating Liveable & Bikeable Cities - Cebollada, Àngel (Documents d'Anàlisi Geogràfica, 2015)
Dextre, Juan Carlos; Hughes, Mike y Bech, Lotte (2013) Cyclists & Cycling Around the World. Creating Liveable & Bikeable Cities Lima: Fondo Editorial de la Pontificia Universidad Católica del Perú, 334 p. ISBN 978-612-4146-55-8